Capital Adequacy Ratio dan Tingkat Suku Bunga Kredit Terhadap Penyaluran Kredit di Bursa Efek Indonesia - Fitri Malini (Universitas Muhammadiyah Prof. DR HAMKA., 2017)
His study aimed to determine the effect of the Capital Adequacy Ratio (CAR), and the interest rate loans to total lending in the banking companies in the Indonesia Stock Exchange. The method used in this research is the method of explanation, the independent variables used in this study consisted of Capital Adequacy Ratio (CAR), and loan interest rates while the dependent variable is the amount of lending. The population in this study were banking companies in the Indonesia Stock Exchange, samples taken amounted to 10 (ten) companies with the research period between 2009 and 2013. Partially Capital Adequacy Ratio (CAR), significant negative effect on the amount of lending, and loan interest rates are not significant positive effect on the amount of lending. While simultaneously Capital Adequacy Ratio (CAR), and loan interest rates not significant effect on the amount of lending to the banking company in BEI 2009-2013.